PENGENDALIAN SERANGAN RAYAP TANAH PADA BEBAK GEWANG MENGGUNAKAN BAHAN PENGAWET ALAMI EKSTRAK TUBA (Derris eliptica) - Sigit B Prabawa; Ermi E Koeslulat; W O Muliastuty (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2019)
People from East Nusa Tenggara generally use Gewang midribs for walls and ceilings. However this midribs contains ingredients that can be attacked by organisms such as termites. To overcome this, preservation action is needed. Conventional preservatives commonly contain ingredients that are less environmentally friendly, expensive and not easily available. Therefore it is necessary to find a natural preservative from the flora species more suitable for people. The purpose of this study was to obtain data and information about the effect of the concentration of natural preservatives from Tuba extract on the Gewang midribs. Tuba extract was obtained through the maceration using methanol. Preservation was carried out by soaking the Gewang midribs samples in to tuba extract solution with the consentration (gr/liter) of 0 (control), 4, 9, 16, 25 and 36 for 24 hours at room temperature. The effectiveness of preservatives was done using soil termites test. The results showed that tuba extract had a very significant effect on decreasing the weight of the sample and increasing the quality class of gewang midirb from class IV to II. It is recommended that preserving gewang midribs can use tuba extract with a concentration at least of 4 gr per liter of water